STRATEGI PEMASARAN PT. JAN’S TOURS & TRAVEL SERVICE DALAM MENINGKATKAN KEDATANGAN WISATAWAN AUSTRALIA - Tettie Setiyarti; Ida Ayu Made Adnyani; Ida Bagus Radendra Suastama (STIMI Handayani Denpasar, 2019)
Bali as one of the tourist destinations in Indonesia that is able to attract many domestic tourists or foreign tourists have developed many forms of facilities and infrastructure. One of them is the needs of tourists about information or booking tour packages that can be accessed easily.The purpose of this research is to know the marketing strategy in order to increase the arrival of Australian tourists at PT Jan’s Tours & Travel Service in marketing and selling the product to the consumer as well as supporting factors and inhibiting the increase of tourist arrivals. This research method through data collecting technique by observation, in-depth interview (interview) and documentation with qualitative descriptive technique. Result of this study is with the implementation of the 7P strategy able to increase the level of visits of foreign tourists, especially those from Australia